Wear-resistant stone plastic plate and preparation method thereof
By combining modified wear-resistant paper with polyurethane-based adhesive, the preparation process of stone-plastic composite panels is optimized, solving the problems of production efficiency and wear resistance of stone-plastic composite panels in the existing technology, and realizing efficient and stable production of wear-resistant stone-plastic composite panels.
Patent Information
- Application Number
- CN202611162655.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-11-06
AI Technical Summary
Existing methods for preparing stone-plastic composite panels have limitations such as difficulty in meeting actual production schedules, high operating costs, and insufficient wear resistance and interlayer adhesion, leading to problems such as easy cracking, peeling, and delamination of the products, making stable mass production impossible.
By combining modified wear-resistant paper with polyurethane-based adhesive, and through continuous heating, segmented drying, and hot pressing processes, the structure and processing parameters of the board are optimized to achieve toughening and bonding of the wear-resistant paper, eliminate internal stress, and improve interlayer adhesion by using polyvinyl chloride decorative film.
This technology enables stable production of wear-resistant stone-plastic panels in a single hot-pressing process, improving the yield rate and avoiding problems such as cracking, peeling, and delamination. It meets market demands for wear resistance and service life, and has high market value.
Smart Images

Figure CN123040441A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of sheet metal technology, specifically to a sheet metal with high wear resistance and its stable preparation method. Background Technology
[0002] Stone-plastic composite (SPC) panels are a new type of floor decoration material. They are usually made from natural stone powder (such as calcium carbonate powder) and polyvinyl chloride resin. They have an extremely low coefficient of thermal expansion, and therefore their moisture resistance is far superior to that of solid wood and wood composite boards. As a result, SPC panels have been used more and more widely in recent years.
[0003] Faced with increasingly stringent market demands, improving the physical properties of stone-plastic composite (SPC) panels, such as wear resistance, has become a popular development trend. For example, patent application number 201711366427.3 discloses a method for manufacturing reinforced flooring, which includes the following steps: Step A, impregnating wear-resistant paper, decorative paper, and balancing paper; Step B, drying the impregnated wear-resistant paper, decorative paper, and balancing paper; Step C, treating the upper and lower surfaces of the base layer to improve their surface roughness; Step D, applying adhesive to the upper and lower surfaces of the base layer; Step E, stacking the wear-resistant paper, decorative paper, base layer, and balancing paper from top to bottom; Step F, pressing the wear-resistant paper, decorative paper, base layer, and balancing paper together using a cold-in, cold-out hot-pressing method. This preparation method can produce composite panels with excellent wear resistance, using SPC as the core material, and can overcome the problems of deformation and weak bonding between layers that occur during the manufacturing process. However, in actual production, this preparation method suffers from difficulties in implementation or excessively high operating costs, making it difficult to put into practical use. For example, in the cold-in and cold-out steps of the hot-pressing process in step F, the hot-pressing equipment used typically only has a fast heating function. However, existing technology requires it to be cooled down to a working temperature close to the ambient temperature after the high-temperature hot pressing is carried out. The cooling operation of the equipment during this period is too time-consuming and difficult to match the actual production and processing rhythm.
[0004] Therefore, there is an urgent need to improve the preparation method of wear-resistant stone plastic board in order to simplify the preparation method and meet the actual production and processing needs. Summary of the Invention
[0005] One of the objectives of this invention is to provide a method for preparing wear-resistant stone plastic boards that is in line with actual production rhythm, has simple steps, and can ensure a high product qualification rate.
[0006] The second objective of this invention is to provide a wear-resistant stone-plastic board prepared by the above-mentioned method, which has physical properties such as wear resistance that meet the requirements for use.
[0007] This invention is achieved through the following technical solution:
[0008] In a first aspect, the present invention provides a method for preparing a wear-resistant stone-plastic board, comprising: S1. impregnating wear-resistant base paper in melamine resin, controlling the impregnation amount to be 150~250%, and performing drying and pre-curing after impregnation to obtain modified wear-resistant paper; S2. coating the modified wear-resistant paper with polyurethane-type adhesive, controlling the coating amount to be 10~20 g / m². 2 S3. After coating, dry to obtain adhesive-modified wear-resistant paper; S4. Stack modified wear-resistant paper or adhesive-modified wear-resistant paper, stone-plastic substrate board, decorative color film and adhesive-modified wear-resistant paper in sequence from bottom to top to form a stack, wherein the adhesive-containing surface of any adhesive-modified wear-resistant paper faces the direction of the stone-plastic substrate board; S5. Perform hot pressing on the stack, control the hot pressing temperature to 135~145℃, the hot pressing pressure to 10~15MPa, the holding pressure duration to 40~60min, and cool after hot pressing to obtain wear-resistant stone-plastic board.
[0009] In composite stone-plastic panels, melamine resin-modified wear-resistant paper is typically used to enhance surface abrasion resistance. However, this paper also suffers from drawbacks such as high fiber rigidity and poor high-temperature toughness. During the high-temperature, high-pressure hot-pressing process, the composite stone-plastic panel is susceptible to cracking, peeling, and localized flaking of the wear-resistant paper due to the combined effects of high temperature, extrusion, and resin curing shrinkage stress. This results in a high product scrap rate and hinders stable mass production. Furthermore, the market demand for aesthetically pleasing panels is increasing, often requiring the addition of decorative films to meet market requirements. However, relying solely on conventional hot-pressing to bond the wear-resistant paper and decorative films can lead to insufficient interlayer adhesion, resulting in surface delamination and peeling after prolonged use.
[0010] Based on the above requirements, this invention achieves normal processing of composite stone-plastic composite boards by modifying the wear-resistant base paper, selecting the bonding adhesive, optimizing the board structure, and optimizing the processing parameters during hot pressing. This ensures that the processed composite stone-plastic composite boards meet market demands for wear resistance, service life, and appearance.
[0011] In this invention, the melamine resin used improves the abrasion resistance of the base paper, while the polyurethane adhesive enables bonding between the modified abrasion-resistant paper and the decorative film and stone-plastic substrate. Simultaneously, the two materials work synergistically. Firstly, unlike conventional techniques where the polyurethane adhesive is coated onto the decorative film, this invention coats the modified abrasion-resistant paper with the polyurethane adhesive. This allows the adhesive to penetrate the base paper, toughening the paper base and overcoming defects such as high-temperature cracking and peeling at the source during the base paper modification stage. Secondly, the selection of melamine resin and polyurethane adhesive in this invention allows for cross-linking, enhancing adhesion and preventing the modified abrasion-resistant paper from peeling off the decorative film during subsequent hot-pressing processes.
[0012] Based on the appropriate selection of materials, this invention adopts a symmetrical arrangement of two layers of modified wear-resistant paper placed on the top and bottom of the stone-plastic substrate. This ensures that the shrinkage and tensile stresses in the board are symmetrical during the subsequent hot pressing process, thereby effectively offsetting the internal stress of the board and ensuring the dimensional stability of the board during the hot pressing process.
[0013] Based on the selection of the board structure and materials, this invention utilizes a single hot-pressing process to prepare the board. The chosen processing parameters, such as the hot-pressing temperature, are perfectly matched to the selected board structure and materials. The selected hot-pressing temperature ensures that the polyurethane adhesive reaches the cross-linking activation temperature threshold. Following the pre-coating and drying curing, the hot-pressing stage achieves secondary curing, stabilizing the fiber structure in the wear-resistant base paper, preventing cracking during later use, and ensuring high adhesion strength between the adhesive and the wear-resistant base paper, preventing delamination in the board. The selected hot-pressing pressure ensures the expulsion of air from between the layers of the wear-resistant base paper, preventing delamination and delamination. Finally, based on the board structure of this invention, a longer holding time is used to slowly release the internal stress generated by the multi-layer composite material under a prolonged constant temperature and pressure environment. This allows the multi-layer material to form synchronously and shrink uniformly, maximizing the stress balance effect brought about by the modified wear-resistant paper on both sides. Ultimately, the warpage deformation of the finished product can be controlled to within 0.5mm.
[0014] As a further improvement of the present invention, in S1, a continuous heating segmented drying method is adopted during the drying and pre-curing process. Several drying sections with different drying temperatures are continuously arranged, with the drying temperature controlled at 125~135℃ and the duration of each drying section being 40~50s. The continuous heating segmented drying method can basically include a low-temperature pre-drying section, a medium-temperature curing section, and a high-temperature setting section. The low-temperature pre-drying section can volatilize most of the free water and low-molecular-weight volatiles in the resin, avoiding problems such as resin bubbling and wear-resistant paper bubbling caused by sudden high-temperature heating. The medium-temperature curing section can achieve preliminary cross-linking and pre-curing of the melamine resin, ensuring that it does not leak. The high-temperature setting section can complete the semi-curing of the resin, but retain trace amounts of active groups to facilitate cross-linking and bonding with the subsequent polyurethane-based adhesive. This continuous heating segmented drying method can prevent excessive temperature differences between the inside and outside of the modified wear-resistant paper from generating internal stress, achieving the effect of relieving the rigidity of the wear-resistant paper in advance, and laying the groundwork for subsequent toughening with polyurethane-based adhesive.
[0015] As a further improvement of the present invention, in S2, the drying temperature after coating is 80~100℃ and the drying time is 60~80s. Under these processing conditions, the cross-linking between the polyurethane-type adhesive and the melamine resin is completed, and the primary curing of the polyurethane-type adhesive is achieved, providing a basis for the secondary curing in the subsequent thermal processing steps.
[0016] As a further improvement of the present invention, in S1, the melamine resin also contains abrasion-resistant filler. The addition of abrasion-resistant filler can further improve the abrasion resistance of the modified abrasion-resistant paper. This modification process complements the preparation method of the present invention, ensuring that the modification does not lead to a decrease in the yield of the finished board. For example, in the preferred continuous heating segmented drying process of the present invention, the medium-temperature curing stage not only achieves the goal of preliminary cross-linking and pre-curing but also locks in the abrasion-resistant filler to prevent precipitation, thereby ensuring that the abrasion-resistant modification can be achieved.
[0017] As a further improvement of the present invention, the wear-resistant filler is aluminum oxide.
[0018] As a further improvement of the present invention, in S1, the wear-resistant base paper is a fiber paper. It has the required wear resistance and toughness, and on this basis, it has sufficient pores at the microscopic level to absorb melamine resin, polyurethane-type binder, and even wear-resistant filler, thus providing ample room for its own modification and the improvement of the adhesive properties of polyurethane-type binder.
[0019] As a further improvement of the present invention, the decorative film used in S3 is a polyvinyl chloride decorative film. On the one hand, its coefficient of thermal expansion is matched with that of the other materials, so that stress can be uniformly transmitted during the processing and use of the board. On the other hand, the polyvinyl chloride decorative film can also cross-link with the polyurethane adhesive under the hot pressing working conditions of the present invention. Therefore, its synergistic bonding effect with other materials at the chemical bonding level further avoids the delamination of the board during the hot processing, so that the processed board meets the product requirements.
[0020] As a further improvement of the present invention, the thickness of the stone-plastic substrate is 5-7mm, which accounts for 95-97% of the thickness of the wear-resistant stone-plastic board.
[0021] As a further improvement of the present invention, the stone-plastic substrate is a polyvinyl chloride calcium carbonate stone-plastic extruded substrate.
[0022] Secondly, the present invention provides a wear-resistant stone-plastic board, which is prepared by any of the above-mentioned methods for preparing wear-resistant stone-plastic boards. The wear-resistant stone-plastic board comprises, from top to bottom, a top wear-resistant layer, a decorative color film layer, a stone-plastic substrate layer, and a bottom wear-resistant layer.
[0023] The beneficial effect of this invention is that it improves the overall preparation method of wear-resistant stone plastic board by the indispensable cooperation among material selection, board structure optimization and processing parameter optimization in hot pressing.
[0024] If modified wear-resistant paper is used with a traditional single-sided structure, the stress in the material is difficult to eliminate during the finished product processing, and the processed board will still warp; if the board structure in this invention is used with ordinary wear-resistant base paper, material delamination will occur after hot pressing, causing the board to be scrapped; if only the parameters of hot pressing are adjusted, without modified wear-resistant paper and the corresponding board structure, it is impossible to solve the four major defects of wear resistance, cracking, deformation and delamination at the same time.
[0025] In summary, the preparation method of this invention not only requires a single heat treatment to obtain the sheet material, but also improves the processing efficiency and reduces manufacturing costs. Furthermore, it overcomes problems such as easy cracking, peeling, delamination, and detachment of the sheet material during processing, ensuring a high yield rate. In addition, the processed sheet material has excellent wear resistance in its top wear-resistant layer and is not prone to cracking after long-term use, thus extending the service life of the sheet material and meeting increasingly stringent market requirements, thereby possessing high market value. Attached Figure Description
[0026] The accompanying drawings are provided below to illustrate the preferred embodiments of the invention and to aid in understanding the objectives and advantages of the invention, wherein:
[0027] Figure 1This is a schematic diagram of the layer layout in a wear-resistant stone-plastic board. Detailed Implementation
[0028] The present invention will now be described in further detail with reference to the accompanying drawings and embodiments.
[0029] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without inventive effort are within the scope of protection of this invention.
[0030] Example 1:
[0031] This embodiment provides a wear-resistant stone-plastic board, such as Figure 1 As shown, it consists of a top wear-resistant layer 1, a decorative color film layer 2, a stone-plastic substrate layer 3, and a bottom wear-resistant layer 4, from top to bottom.
[0032] The wear-resistant stone-plastic board is prepared using the following method:
[0033] S1. The wear-resistant base paper is impregnated in melamine resin, and the impregnation amount is controlled at 150~250%. After impregnation, drying and pre-curing are carried out to obtain modified wear-resistant paper. In this embodiment, the wear-resistant base paper is fiber paper. During drying and pre-curing, continuous heating and segmented drying are adopted, with a total of three stages. The drying temperature of the first stage is 125℃ and the duration is 40s, the drying temperature of the second stage is 130℃ and the duration is 40s, and the drying temperature of the third stage is 135℃ and the duration is 40s.
[0034] S2. Apply a polyurethane-based adhesive to the modified abrasion-resistant paper, controlling the coating amount to approximately 15 g / m². 2 After coating, it is dried at 80℃ for 70s to complete the first curing of polyurethane-type adhesive and achieve initial cross-linking with melamine resin, thereby obtaining adhesive-modified wear-resistant paper.
[0035] S3. In this embodiment, modified wear-resistant paper, stone-plastic substrate board, decorative color film, and adhesive-containing modified wear-resistant paper are stacked sequentially from bottom to top to form a laminate. The decorative color film used is a conventional polyvinyl chloride decorative color film, and the stone-plastic substrate board is a conventional polyvinyl chloride calcium carbonate stone-plastic extruded substrate. The adhesive-containing modified wear-resistant paper placed on top of the stone-plastic substrate board has its adhesive side facing down towards the stone-plastic substrate board. In this embodiment, the modified wear-resistant paper without adhesive coating is used below the stone-plastic substrate board. Since there is no decorative color film or other structure between it and the stone-plastic substrate board, the melamine resin carried in the wear-resistant paper can also complete the bonding with the stone-plastic substrate board under hot pressing. The adhesive-containing modified wear-resistant paper located above the stone-plastic substrate board can achieve a tight bond between the modified wear-resistant paper, decorative color film, and stone-plastic substrate board using the coated polyurethane adhesive, so as to ensure that no delamination or peeling occurs after hot pressing.
[0036] S4. Perform hot pressing on the stacked blanks, controlling the hot pressing temperature to be about 140℃, the hot pressing pressure to be 12MPa, and the holding pressure duration to be 60min. After hot pressing, remove the board and cool it to obtain the final product wear-resistant stone plastic board.
[0037] In this embodiment, the modified wear-resistant paper layer is approximately 0.08 mm thick, the selected stone-plastic substrate is 5 mm thick, and the final wear-resistant stone-plastic board has a total thickness of approximately 5.21 mm. The thickness of the stone-plastic substrate accounts for approximately 95.9% of the total thickness of the wear-resistant stone-plastic board. This ensures that the board provides the main strength support for the board as a whole and guarantees that the board retains the beneficial effects of the stone-plastic substrate, such as waterproofing, moisture resistance, formaldehyde-free environmental protection, and dimensional stability.
[0038] Example 2:
[0039] This embodiment provides a wear-resistant stone-plastic board, which differs from the one in Embodiment 1 in that:
[0040] In step S3 of the preparation method, adhesive-modified wear-resistant paper, stone-plastic substrate board, decorative color film, and adhesive-modified wear-resistant paper are stacked sequentially from bottom to top to form a laminate; wherein the adhesive-modified wear-resistant paper placed below the stone-plastic substrate board has its adhesive-containing surface facing upwards and towards the stone-plastic substrate board.
[0041] In step S4 of the preparation method, the hot pressing temperature is controlled at 145℃, the hot pressing pressure is 15MPa, and the holding time is 55min.
[0042] In this embodiment, the thickness of the modified wear-resistant paper layer is about 0.12 mm, the thickness of the selected stone-plastic substrate is 7 mm, and the total thickness of the final wear-resistant stone-plastic board is about 7.29 mm. The thickness of the stone-plastic substrate accounts for about 96.1% of the thickness of the wear-resistant stone-plastic board.
[0043] Example 3:
[0044] This embodiment provides a wear-resistant stone-plastic board, which differs from the one in Embodiment 1 in that the melamine resin used in preparation method S1 also contains wear-resistant filler, which is aluminum oxide particles used in this embodiment.
[0045] Performance testing:
[0046] The wear-resistant stone-plastic composite boards in Examples 1-3 were subjected to surface appearance testing, abrasion resistance testing, scratch resistance testing, and warpage testing under high-temperature conditions. For test methods where specific conditions were not specified, national standards were generally followed. If no corresponding national standard exists, general international standards, conventional conditions, or conditions recommended by the manufacturer were followed. In this example, surface appearance testing required exposing the boards to 80°C for 6 hours to observe their surface condition. Abrasion resistance testing was conducted according to standard BS EN 13329; scratch resistance testing was conducted according to standard ISO 1518-1; and warpage testing was conducted according to standard ISO 23999.
[0047] The performance test results of each group of boards are shown in Table 1:
[0048] Table 1 Summary of Plate Performance Test Results
[0049]
[0050] The test results above show that the wear-resistant stone-plastic composite board prepared by the method of this invention can maintain its surface without cracking, fine lines, or peeling under high temperature conditions. Under the corresponding standard test conditions, each group of boards requires the grinding head to rotate at least 6000 rpm to break the surface and expose the stone-plastic substrate. Each group of boards requires a force of at least 10N to leave scratches. Thus, the boards have excellent wear resistance. Furthermore, under the corresponding standard test conditions, the boards have a warpage of less than 0.5mm, which meets the requirements for board warpage deformation in flooring and other usage scenarios.
[0051] In summary, the preparation method of this invention enables the efficient production of high-wear-resistant sheets using a relatively simple one-time hot-pressing process, and the yield of the processed sheets is high. Therefore, both the preparation method and the obtained wear-resistant stone-plastic sheets have good prospects for market promotion and use.
[0052] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a wear-resistant stone-plastic board, characterized in that, Includes: S1. Impregnate the wear-resistant base paper in melamine resin, controlling the impregnation amount to be 150~250%. After impregnation, carry out drying and pre-curing to obtain modified wear-resistant paper. S2. Apply a polyurethane-type bonding adhesive to the modified wear-resistant paper, controlling the coating amount to be 10~20 g / m². 2 After coating, drying yields a glue-modified abrasion-resistant paper. S3. The modified wear-resistant paper or the adhesive-containing modified wear-resistant paper, the stone-plastic substrate board, the decorative color film, and the adhesive-containing modified wear-resistant paper are stacked sequentially from bottom to top to form a stack, wherein the adhesive-containing surface of any of the adhesive-containing modified wear-resistant papers faces the direction of the stone-plastic substrate board. S4. Perform hot pressing on the stacked blanks, controlling the hot pressing temperature to be 135~145℃, the hot pressing pressure to be 10~15MPa, and the holding pressure duration to be 40~60min. After hot pressing, cool to obtain wear-resistant stone plastic board.
2. The method for preparing a wear-resistant stone-plastic board according to claim 1, characterized in that, In S1, the drying and pre-curing process adopts a continuous heating segmented drying method, in which several groups of drying sections with different drying temperatures are continuously arranged. The drying temperature is controlled at 125~135℃ and the duration of each drying section is 40~50s.
3. The method for preparing a wear-resistant stone-plastic board according to claim 1, characterized in that, In S2, the drying temperature after coating is 80~100℃ and the duration is 60~80s.
4. The method for preparing a wear-resistant stone-plastic board according to claim 1, characterized in that, In S1, the melamine resin also contains wear-resistant fillers.
5. The method for preparing a wear-resistant stone-plastic board according to claim 4, characterized in that, The wear-resistant filler is aluminum oxide.
6. The method for preparing a wear-resistant stone-plastic board according to claim 1, characterized in that, In S1, the wear-resistant base paper is fiber paper.
7. The method for preparing a wear-resistant stone-plastic board according to claim 1, characterized in that, The decorative film used in S3 is a polyvinyl chloride decorative film.
8. The method for preparing a wear-resistant stone-plastic board according to claim 1, characterized in that, The thickness of the stone-plastic substrate is 5-7mm, accounting for 95-97% of the thickness of the wear-resistant stone-plastic board.
9. The method for preparing a wear-resistant stone-plastic board according to claim 1, characterized in that, The stone-plastic substrate is a polyvinyl chloride calcium carbonate stone-plastic extruded substrate.
10. A wear-resistant stone-plastic board, characterized in that, The wear-resistant stone-plastic board is prepared by any one of claims 1 to 8, and it comprises, from top to bottom, a top wear-resistant layer (1), a decorative color film layer (2), a stone-plastic substrate layer (3), and a bottom wear-resistant layer (4).
Citation Information
Patent Citations
A method for manufacturing laminate flooring
CN108099338B
